(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Within the context of the Cervantine criticism, new reasons are discussed in this article to consider Don Quixote as the first modern novel, from the point of view of Mijail Bakhtin writings. Cervantes’s great work would not only overcome the monologic line, but more precisely it would constitute an intersection between the monologic and dialogic lines of the Universal Literature. This would be evident in the mixture of higher and lower literary genre and in the opposition between Don Quixote´s sublime and knight-like speeches and Sancho´s folk and popular speeches. This truly dialogic relationship would be based upon the intertextuality of Cervantes’s work with the Socratic dialog and the Mineppean satire of antiquity.